Penggunaan Paylater Dalam Prespektif Ekonomi Islam - Handayani, Khairunnisa; Nurfadillah, Putri Azhar; Lince, Tinur; Robiansyah, Firman Robiansyah4 (Al - Muamalat: Jurnal Hukum dan Ekonomi Syariah, 2024)
Abstract Pay later has become a popular online payment trend among the public, especially millennials. Ease of access and payment flexibility are the main attractions of this feature. However, from an Islamic economic perspective, the use of Pay later needs to be further studied because it has the potential to contain elements of usury (riba ). This study aims to analyze Islamic law related to the use of Pay later in online transactions. The method used is literature study by collecting data from various reliable sources, such as academic journals, books, and fatwas from scholars. The research results show that Pay later contains elements of usury because it charges interest and fines to users. This is contrary to the principles of Islamic economics which prohibit usury in all its forms. In addition, the Pay later payment mechanism does not comply with the qardh akad which is permissible in Islam. Based on these findings, it is concluded that the use of Pay later is not justified in Islamic law. Muslims are urged to avoid using Paylater and choose payment methods that are in accordance with Islamic law.